Thomas Hobbes and the Political Philosophy of Glory - Slomp, G. author. aut Link
XII, 194 p.
Keywords: Hobbes's philosophical discourse is deconstructed as the interplay of the drama of individual behaviour as perceived by rational agents and the detached analysis of conflict by a political geometer . The author solves some long-standing problems in Hobbesian political philosophy (e.g., the role of glory, Hobbes' pessimism) and shows the consistency of Hobbes' attempt to derive absolutism as the only stable political association. Although based on extensive textual analysis of Hobbes' works and correspondence, the book is an exercise in political philosophy that students will find iconoclastic and experts challenging.